Stochastic modeling of global software development teams - Santos, Alan Ricardo dos (2012)
Projects performance evaluation is an important aspect of global software development. Companies and institutions can obtain benefits by the use of performance evaluation of teams working in different sites. The objective of this work is to discuss a stochastic model definition to performance evaluation of Follow-The-Sun (FTS) projects aspects such as time, quality and cost. Example issues that can be addressed using this FTS model are provided with performance evaluation results.